Peculiarities of legal regulation of commission contract by the legislation of the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2018)
The article is devoted to the study of the problems of recognizing a commission’s contract as invalid, namely from the point of view of establishing specific conditions for declaring it invalid and also, the legal regulation of the relations of the parties after the recognition of mentioned contract as invalid. The relevance of the research topic is determined by several factors based on the need to study issues of scientific-theoretical, legislative nature. As a special type of contract, the contract of commission, along with domestic legislation, is governed by the laws of Germany, France, and Switzerland. In countries with a dualistic private law system, a commission agreement is treated as a trade transaction and is governedby trade codes. The most complete contract and related relations are settled in GSU and SHOZ.In the modern capitalist turnover, a commission agreement is mediated by various kinds of bankingoperations, the subject of which is primarily securities. In the regulation of such operations a specialplace is occupied by standard contracts developed by banks. This contractual form is also used for thepurchase and sale of goods, chartering and other transactions, not only in domestic but also in foreigntrade as a means of penetrating markets. The importance of this study is growing due to the fact that thistype of contract is common not only in the Kazakhstan market, but also around the world, and becauseof the standard form of a contract, in practice, problems often arise with the termination and invalidation.In addition, in domestic science there is no comprehensive theoretical study of this topic from alegal point of view. This work aims to determine the conditions, the consequences of the recognition ofthe contract commission void. In the course of the study, general scientific, historical and comparativeanalysis methods were used. The legal analysis carried out by the authors makes it possible to providerecommendations on how to improve the national legal regulation of these problems.Key words: committent, contract of commission, restitution, consequences of a transaction beingdeclared invalid.